Gotham’s Mirror: Althusserian Reflections in Tod Phillips’ Joker and Contemporary America - Azra Ghandeharion (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This study critically examines Todd Phillips’ Joker (2019) through the theoretical framework of Louis Althusser, identifying a lacuna in Iranian academic discourse—the exploration of political narratives in Hollywood’s comic book adaptations. While Joker achieved commercial success akin to its superhero film counterparts, its nuanced political commentary sets it apart. This paper interrogates the film’s depiction of Althusser’s ideological and repressive state apparatuses within the capitalist milieu of the fictional Gotham City. Through a meticulous analysis of pivotal scenes, the paper elucidates the strategies employed by Gotham’s ruling entities to perpetuate hegemony, drawing parallels with the political landscape of contemporary America. The research employs a qualitative content analysis methodology, enabling a nuanced interpretation of the film’s subtextual elements that resonate with the socio-political climate of the United States, particularly during the Trump era. Conclusively, Joker emerges not merely as a cinematic experience but as a reflective social commentary, mirroring the class struggle and the political machinations prevalent in American society.